Effects of ultra-processed foods on the liver: insights from gut microbiome and metabolomics studies in rats - Shi, Liping; Li, Zhuoyuan; Ma, Xiaojun; Wang, Junru; Wu, Yueping; Zhu, Yongbin; Wang, Yanrong; Yang, Yue; Luo, Minxiu; Li, Jiangping; Sun, Xian; He, Shulan (Frontiers in Nutrition, 2025)
PurposeHigh consumption of Ultra-processed foods (UPF) have been identified as a potential risk factor for Non-alcoholic fatty liver disease (NAFLD). Nevertheless, there is limited empirical evidence regarding the impact of UPF, which are typical combination of processed foods, on liver health through alterations in gut microbiota and metabolic processes. We aim to examine the potential impact of UPF on liver health and to explore the role of gut microbiota and metabolites.MethodsThis study used Sprague–Dawley rats to mimic modern UPF diets for 90 days. Some serum biochemical indices, inflammatory factors, oxidative stress markers, hematoxylin–eosin (HE) staining of the liver, 16S ribosomal RNA (rRNA) and Liquid chromatography-mass spectrometry (LC–MS) of rat feces were detected.ResultsThe UPF diet-induced simple steatosis of the liver in rats without affecting the levels of IL-6, GSH, MDA, and SOD. Additionally, it modified the gut microbiota, increasing potentially harmful bacteria, such as norank_f__Desulfovibrionaceae and Staphylococcus, while also elevating the relative abundance of potentially beneficial bacteria, including Dubosiella and Allobaculum. Furthermore, the consumption of UPF led to a metabolomic disorder characterized by disruptions in the sphingolipid signaling pathway, sulfur relay system, and arachidonic acid metabolism.ConclusionIn conclusion, the findings of this study indicate that the consumption of UPF influences the development of simple hepatic steatosis, potentially through alterations in gut microbiota and metabolomics.